1987
DOI: 10.1172/jci112920
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of oleate from albumin solutions by rat liver. Failure to detect catalysis of the dissociation of oleate from albumin by an albumin receptor.

Abstract: The hepatic removal of albumin-bound substances from plasma requires that they dissociate from albumin. Using indirect methods, we and others have proposed that dissociation may be catalyzed by interaction of albumin with the liver cell surface. This study looked for direct evidence of catalysis by comparing the rate of dissociation of oleate from albumin in vitro with the rate observed within the sinusoids of perfused rat liver. No evidence for catalysis was found. The rate of hepatic oleate removal from dilu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
35
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(43 citation statements)
references
References 37 publications
8
35
0
Order By: Relevance
“…We have recently argued that uptake of fatty acids requires that they first enter the unbound pool by spontaneous dissociation from albumin, and have shown that at lower albumin concentrations dissociation may limit the uptake rate by limit- ing the availability of unbound fatty acid within the hepatic sinusoids (5). Because unbound fatty acids make up < 0.02% of the total fatty acid in plasma, such a sequence requires an extraordinarily efficient cellular mechanism for removing unbound fatty acids from the sinusoids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently argued that uptake of fatty acids requires that they first enter the unbound pool by spontaneous dissociation from albumin, and have shown that at lower albumin concentrations dissociation may limit the uptake rate by limit- ing the availability of unbound fatty acid within the hepatic sinusoids (5). Because unbound fatty acids make up < 0.02% of the total fatty acid in plasma, such a sequence requires an extraordinarily efficient cellular mechanism for removing unbound fatty acids from the sinusoids.…”
Section: Resultsmentioning
confidence: 99%
“…Hepatic uptake of unesterified fatty acids from plasma proceeds rapidly despite binding of > 99.98% of plasma fatty acids to serum albumin. It has been suggested that this high efficiency reflects a direct interaction ofthe albumin-fatty acid complex with the liver cell membrane (2-4), although we no longer favor this view (5). On the other hand, the uptake mechanism would need to be extraordinarily efficient to account for observed uptake rates if cellular uptake draws only on the small unbound fatty acid pool in plasma (3).…”
Section: Introductionmentioning
confidence: 86%
“…Therefore, the FA dissociation from albumin is commonly not thought to be a rate-limiting step for FA transport into myocardial tissue. [20][21][22] The transfer of FA from plasma to cardiac cells does not involve solely a phase boundary (plasmacapillary wall) process; it also involves a sequence of membrane and aqueous phase translocation processes. These include passage of FAs across the capillary wall and movement through the intercellular space before they are presented to the cardiomyocytes.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…As most tissues have limited or no capacity to synthesize LCFA on their own, they depend on LCFA uptake from the circulation. Both the liver and the heart are extremely efficient in extracting LCFA from the blood (1,4). The endothelial layer is the first barrier to be traversed by LCFA before they can be metabolized by the underlying parenchymal tissue.…”
mentioning
confidence: 99%